Chi-miR-4110 promotes granulosa cell apoptosis by targeting Sma- and Mad-related protein 2 (Smad2) in the caprine ovary. - Xiaopeng An; Yuxuan Song; Jinxing Hou; Yue Zhang; Kaiwen Chen; Haidong Ma; Xinyan Zhao; Guang Li; Kexin Gao; Shan Wang; Binyun Cao; Yueyu Bai (PLoS ONE)
Follicular atresia mainly results from the apoptosis of granulosa cells (GCs). Whilst our previous investigations examined the role of chi-miR-4110 in regulating ovarian function, the present study detected the role of chi-miR-4110 in GC development. We transfected caprine GCs cultured in vitro with chi-miR-4110 mimics. Results revealed that chi-miR-4110 decreased mRNA and protein levels of Smad2 by targeting its 3'-untranslated region (3'UTR). FoxC1 and Sp1 mRNA and protein levels markedly increased, whereas those of bHLHe22 significantly decreased (P<0.01 or 0.05) in GCs transfected with the chi-miR-4110 mimics. Further studies revealed a significantly higher number of apoptotic cells in GCs transfected with the chi-miR-4110 mimics (P< 0.05) than in GCs transfected with mimics negative control. GCs transfected with the chi-miR-4110 mimics exhibited significantly increased mRNA and protein levels of the pro-apoptotic gene Bax (P<0.01) and significantly decreased expression levels of the anti-apoptotic gene BCL-2 (P<0.01). Smad2 interference (Si-1282) results were consistent with those of the chi-miR-4110 mimics. Previous reports and our results showed that chi-miR-4110 increases Sp1 expression by repressing Smad2. The increase in Sp1 induces p53-upregulated modulator of apoptosis, which increases the relative abundance of Bax and causes caprine GC apoptosis. Our findings may provide relevant data for the investigation of miRNA-mediated regulation of ovarian functions.